Edukasi Nutrisi Remaja: Sugar-Sweetened Beverages (SSB) - Simatupang, Dhea Pebri A. C.; Wisnuwardani, Ratih Wirapuspita (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
The 2023 Indonesian Health Survey (SKI) indicates a 5.6% prevalence of obesity among adolescents, while national obesity in adults has risen to 23.4%. High consumption of Sugar-Sweetened Beverages (SSBs) among adolescents is a risk factor for obesity and other chronic diseases.To address this issue, a community service program was conducted at SMK Negeri 1 Tenggarong with the aim of improving nutrition literacy and reducing SSB consumption. The program involved 30 students and employed an action research design with a cross-sectional approach.Evaluation was carried out through pre-test and post-test questionnaires containing 10 questions to assess nutrition literacy and SSB consumption. The Wilcoxon test was used to analyze differences in knowledge scores before and after the education intervention.Results showed a significant improvement in students' nutrition literacy after participating in the program. This program is expected to contribute to raising awareness about the negative impacts of SSBs and promoting healthy lifestyle behaviors among adolescents.